Insight into the cytotoxicity of polynuclear Cu(I) camphor complexes. (17th February 2015) - Fernandes, Tiago A.; Mendes, Filipa; Roseiro, Alexandra P.S.; Santos, Isabel; Carvalho, M. Fernanda N.N.
Graphical abstract: The cytotoxic activity of Cu(I) camphor complexes against the cancer cell line HT29 depends on their structure, characteristics of the camphor ligand and the halide co-ligand. The polymer [(CuCl)4 m -C6 H4 (NC10 H14 O)2 ] displays a IC50 value similar to that of cisplatin . Abstract: Three new polynuclear Cu(I) camphor complexes, [(CuBr)2 ( p -H2 NC6 H4 )NC10 H14 O] n (2d ), [(CuCl)4 m -C6 H4 (NC10 H14 O)2 ] n (5f ) and [(CuBr)4 p -C6 H4 (NC10 H14 O)2 ] n (6e ), were synthesized and their cytotoxicity, as well as that of the former reported compounds [(CuX)2 (YNC10 H14 O)] n (X = Cl; Y = NMe2 (1a ), NH2 (1b ), NHMe (1c ), (H2 NC6 H4 )NC10 H14 O (1d ); X = Br; Y = NMe2 (2a )), [Cu(Me2 NNC10 H14 O)2 (μ-X)2 ] (X = Cl (3a ), Br (4a )) and [(CuCl)4 p -C6 H4 (NC10 H14 O)2 ] (5f ), were evaluated against the human colon adenocarcinoma cancer cell line HT29 using the colorimetric method (MTT assay). The calculated IC50 values indicate that all the complexes have cytotoxic activity that ranges from high to moderate or low, depending on the characteristics of the camphor ligand and the halide co-ligand. The complexes [(CuCl)4 m -C6 H4 (NC10 H14 O)2 ] (5f, IC50 = 32.0 + 1.1 μM) and [(CuCl)2 (H2 NNC10 H14 O)] n (1b, IC50 = 37.0 ± 1.1 μM) display the lowest IC50 values, while [(CuBr)2 ( p -H2 NC6 H4 )NC10 H14 O] n (2d, IC50 = 119.9 ± 1.1 μM) displays the highest one. The IC50 value for5f approaches that of cisplatin (26.3 + 1.1 μM). No cytotoxic activity was detected for the camphor compounds H2 NNC10 H14 O (b ) and m -C6 H4 (NC10 H14 O)2 (f ), used as ligands. In selected cases, the copper accumulation in the cells was evaluated. No direct relationship was found between the copper uptake and the cytotoxicity of the complexes.